2018
DOI: 10.1007/s13353-018-0458-1
|View full text |Cite
|
Sign up to set email alerts
|

hTERT promoter methylation status in peripheral blood leukocytes as a molecular marker of head and neck cancer progression

Abstract: Cancer cells, including head and neck cancer cell carcinoma (HNSCC), are characterized by an increased telomerase activity. This enzymatic complex is active in approximately 80-90% of all malignancies, and is regulated by various factors, including methylation status of hTERT gene promoter. hTERT methylation pattern has been thoroughly studied so far. It was proved that hTERT is aberrantly methylated in tumor tissue versus healthy counterparts. However, such effect has not yet been investigated in PBLs (periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
(64 reference statements)
2
6
0
Order By: Relevance
“…Although this result needs to be validated in larger case series, it suggests that mhTERT could be one important epigenetic mechanism involved in hTERT regulation, cooperating with other ones to justify the high levels of hTERT mRNA and telomerase activity found in these patients. The second main finding is the prognostic impact of mhTERT high , as just observed in other tumors [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In the multivariable model, we found that only mhTERT high and p63 affected OS, with marginal significance for angioinvasion and absence of MCPyV.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although this result needs to be validated in larger case series, it suggests that mhTERT could be one important epigenetic mechanism involved in hTERT regulation, cooperating with other ones to justify the high levels of hTERT mRNA and telomerase activity found in these patients. The second main finding is the prognostic impact of mhTERT high , as just observed in other tumors [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In the multivariable model, we found that only mhTERT high and p63 affected OS, with marginal significance for angioinvasion and absence of MCPyV.…”
Section: Discussionsupporting
confidence: 76%
“…For the majority of the genes, hypo-methylation of the promoter is fundamental to permit an active transcription [13][14][15]. Nevertheless, several studies showed that hypermethylation of hTERT was paradoxically associated with higher hTERT mRNA levels and telomerase activity depending on the region of interest investigated [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Although several mechanisms cooperate in determining the final telomerase activity, promoter methylation proved to be one of the most relevant ones, singly affecting survival, recurrence, and progression in pediatric brain tumors, meningiomas, head and neck squamous cell carcinoma, leukemias, prostatic adenocarcinoma, and several other tumors [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been validated that hTERT can be detected in free DNAs in serums, and the methylation of hTERT promoter can be a predictor of malignant tumours. 7,8 Hence, this study aims to verify the significance of hTERT promoter methylation in OC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the CPG loci of 92 patients with head and neck cancer (HNSCC) and 53 healthy controls indicated that some sites in HNSCC patients presented a higher frequency of methylation than those in the controls, whilst a contrary finding was observed at another location of CPG. 7 By probing the relationship between gene loci and activity of the hTERT promoter, it was found that the first exon, the first intron and the second exon of 37bp in front of the ATG upstream of the promoter of malignant tumour cells were active, whilst their expression in benign cells was relatively low. 20 Therefore, in this study, the upstream region of the hTERT core promoter was taken as the methylation detection target area.…”
mentioning
confidence: 99%